2015
DOI: 10.1155/2015/981439
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Granulomatosis with Polyangiitis Presenting as Acute Polyneuropathy Mimicking Guillain-Barre Syndrome

Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is a small-vessel vasculitis associated with antineutrophil cytoplasmic antibodies (ANCAs) which commonly affects the peripheral nervous system. A 38-year-old female with a history of asthma presented with a 2-week history of bilateral lower extremity paresthesias that progressed to symmetric ascending paralysis. Nerve conduction studies could not rule out Guillain-Barre syndrome (GBS) and plasmapheresis was considered. Her blood work revealed marked eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Recently published comparative and noncomparative studies of GBS outcomes after treatment with TPE and/or IVIG have consisted primarily of case reports or case series from single institutions in developing countries, at which the choice between TPE and IVIG is largely dependent on economic considerations . Given the established equivalence between TPE and IVIG as effective treatments for GBS, it is important to evaluate patient‐ and hospital‐level characteristics that may affect treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published comparative and noncomparative studies of GBS outcomes after treatment with TPE and/or IVIG have consisted primarily of case reports or case series from single institutions in developing countries, at which the choice between TPE and IVIG is largely dependent on economic considerations . Given the established equivalence between TPE and IVIG as effective treatments for GBS, it is important to evaluate patient‐ and hospital‐level characteristics that may affect treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Keven et al [14] reported the next case presented initially with GBS-like neuropathy, later developing ANCA-positive nephrotic syndrome. At least five other cases of EGPA have been mentioned, all with clinic and neurophysiologic studies suggestive of GBS [15][16][17][18]. Antineutrophil cytoplasmic antibody positivity, eosinophilia and treatment failure with intravenous immunoglobulin led to the correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 There are only two case reports available of PA presenting as a DKA ( Table 1 ). Jiang et al 6 reported an apoplectic GH-secreting adenoma with DKA, while Camara-Lemarroy et al 4 reported a nonadenomatous PA with DKA.…”
Section: Discussionmentioning
confidence: 99%